Obstacles of continuous peripheral nerve block in physiotherapy - Borhan, Muhammad Salman; Mohd Sazali, Zaki Solihin; Aidid, Afif Hakimi; Saw, Yee Hong; Ibrahim, Muhammad Fauzi; Abd Ghani, Muhamad Rasydan; Mohd Hanafiah, Farah Nadia (Universiti Kebangsaan Malaysia, 2021)
Introduction: Perineural local anesthetic infusion also known as continuous peripheral nerve blocks (PNB), is a technique of providing analgesia for multiples days or even weeks by administrating local anesthesia via catheter following insertion of a catheter to peripheral nerve. The technique has been applied to different body regions for a wide range of operations for both hospitalized and ambulatory patients. It is commonly used in providing analgesia post-operation or assisting patient in physiotherapy. Despite of numerous benefits of continuous PNB, various complications have been reported relating to either, needle or catheter insertion or local anaesthetic administered. We hereby report obstacles on a patient with continuous PNB. Case description: A 22-year-old gentleman complicated with right elbow stiffness after underwent two operations for right olecranon process fracture, planned for aggressive physiotherapy. He was subsequently received continuous PNB via supraclavicular approach with continuous infusion. During 17 days of physiotherapy course, the catheter been changed multiple times due to dislodgement despite using topical skin adhesive glue, suture technique, single or double tunneling method, and require alternating insertion via supra-clavicular and costoclavicular approach. Patient also developed Horner’s syndrome invariably despite titrating down infusion rate, limiting boluses volume, minimal local anesthetic concentration, and adjust to multiple staged small boluses. Later, patient complicated with catheter related infection over insertion site with minimal pus formation. Catheter was removed following infection and patient recovered well with a course of oral antibiotic. Conclusion: Despite of peripheral nerve block catheter inserted using aseptic technique under ultrasound guided together with nerve stimulator, dislodgement, Horner Syndrome and infection complications still can happen. Various challenges associated with PNB especially with long course catheter insertion, to have optimal analgesia for physiotherapy with minimal complications. The team and with patient’s co-operation did the best that can be done to help the patient.